Key genetic considerations in the management of suspected hereditary colorectal cancer. (February 2013) - Barrow, Paul J; Clancy, Tara; Evans, D Gareth
SUMMARY  Hereditary bowel cancer syndromes account for up to 5% of colorectal cancer (CRC) incidence. Presentation of CRC under the age of 50 years should alert clinicians to a possible underlying genetic predisposition. This article focuses on Lynch syndrome (hereditary nonpolyposis CRC). Regular bowel screening is effective in reducing the risk of CRC and improving overall survival in Lynch syndrome families. The issues surrounding the clinical diagnostic criteria and the shortcomings of the referral process are described, and it is questioned whether a universal strategy for diagnosis should be employed. This article summarizes the evidence for the benefit of bowel screening and suggests practical steps to help ensure compliance with screening recommendations. Finally, it is discussed how collaboration between geneticists, gastroenterologists and surgeons can inform surgical decision-making for the benefit of the patient.